Oral Contraceptive Use Influences On-Kinetic Adaptations to Sprint Interval Training in Recreationally-Active Women - Schaumberg, Mia Annalies; Stanley, Jamie; Jenkins, David G.; Hume, Emily A.; Janse de Jonge, Xanne A. K.; Emmerton, Lynne M.; Skinner, Tina L. (Frontiers in Physiology, 2020)
Introduction: Oral contraceptive (OC) use influences peak exercise responses to training, however whether OC influences central and peripheral adaptations to exercise training and if this effects exercise performance is not known. This study investigated the influence of OC use on changes in time-to-fatigue, pulmonary oxygen uptake on-kinetics, cardiac output and heart rate on-kinetics and tissue saturation index to four weeks of sprint interval training in recreationally-active women. Methods: Women taking an oral contraceptive (OC; n=25) or experiencing natural menstrual cycles (MC; n=22) completed an incremental exercise test to volitional exhaustion and a square-wave step-transition protocol to moderate (90% of power output at ventilatory threshold) and high intensity (delta50% of power output at ventilatory threshold) exercise to assess time-to-fatigue, pulmonary oxygen uptake on-kinetics, cardiac output and heart rate on-kinetics and tissue saturation index responses prior to, and following 12 sessions of sprint interval training (10 x 1 min efforts at 100-120% peak power output in a 1:2 work:rest ratio) completed over four weeks. Results: Time-to-fatigue increased in both groups following training (p<0.001), with no difference between groups. All cardiovascular on-kinetic parameters improved to the same extent following training in both groups. Greater improvements in pulmonary oxygen up-take kinetics were seen at both intensities in the MC group (p<0.05 from pre-training) but were blunted in the OC group (p>0.05 from pre-training). In contrast, changes in tissue saturation index were greater in the OC group at both intensities (p<0.05); with the MC group showing no changes at either intensity. Discussion: OC use may reduce central adaptations to sprint interval training in women without influencing improvements in exercise performance - potentially due to greater peripheral adaptation. This may be due to the influence of exogenous oestradiol and progestogen on cardiovascular function and skeletal muscle blood flow. Further investigation into female-specific influences on training adaptation and exercise performance is warranted.